Biochar Alleviates Phytotoxicity by Minimizing Bioavailability and Oxidative Stress in Foxtail Millet (Setaria italica L.) Cultivated in Cd- and Zn-Contaminated Soil - Kang, Xirui; Geng, Na; Li, Xu; Yu, Jinpeng; Wang, Hui; Pan, Hong; Yang, Quangang; Zhuge, Yuping; Lou, Yanhong (Frontiers in Plant Science, 2022)
Soil contamination with multiple heavy metals is a global environmental issue that poses a serious threat to public health and ecological safety. Biochar passivation is an efficient and economical technology to prevent heavy metal contamination of Cd; however, its effects on compound-contaminated and weakly alkaline soil remain unclear. Further, the mechanisms mediating the immobilization effects of biochar have not been evaluated. In this study, three biochar, treated at different pyrolytic temperatures (300 [BC300], 400 [BC400], and 500 °C [BC500]) were applied to Cd-/Zn-contaminated soils, and their effects on plant growth, photosynthetic characteristics, Cd/Zn accumulation and distribution in foxtail millet were evaluated. Further, the effect of biochar application on the soil physicochemical characteristics, as well as the diversity and composition of the soil microbiota were investigated. Biochar significantly alleviated the phytotoxicity of Cd and Zn. DTPA (diethylenetriamine pentaacetic acid)-Cd and DTPA-Zn content was significantly reduced following biochar treatment via the transformation of exchangeable components to stable forms. BC500 had a lower DTPA-Cd content than BC300 and BC400 by 42.87% and 39.29%, respectively. The BC500 passivation ratio of Cd was significantly higher than that of Zn. Biochar application also promoted the growth of foxtail millet, alleviated oxidative stress, and reduced heavy metal bioaccumulation in shoots, and transport of Cd from the roots to the shoots in the foxtail millet. The plant height, stem diameter, biomass, and photosynthetic rates of the foxtail millet were the highest in BC500, whereas the Cd and Zn content in each organ and malondialdehyde and hydrogen peroxide content in the leaves were the lowest. Moreover, biochar application significantly increased the abundance of soil bacteria and fungi, as well as increasing the fungal species richness compared to no-biochar treatment. Overall, biochar was an effective agent for the remediation of heavy metal-contaminated soil. The passivation effect of biochar exerted on heavy metals in soil was affected by the biochar pyrolysis temperature, with BC500 showing the best passivation effect.